Arritmia cardíaca - análise do perfil epidemiológico dos pacientes atendidos em ambulatório de cardiologia pediátrica - Haroldo Silvio Reis Mundim; Ana Beatriz Ribeiro Cardoso; Rossano Cesar Bonatto; Carlos Roberto Padovani; José Roberto Fioretto; Juliana Silva Rodrigues Ortiz; Joelma Gonçalves Martin; Fábio Joly Campos; Haroldo Teófilo de Carvalho; Leonardo Tonello Romero (Sociedade Brasileira de Pediatria, 2023)
Cardiac arrhythmias are electrical alterations that may have varied clinical presentations according to their etiological origin, association with adjunct heart problems and degree of impairment of cardiac functioning. Therefore, the epidemiological profile of patients diagnosed with cardiac arrhythmia treated in a Pediatric Cardiology Outpatient Clinic was traced, identifying the most prevalent types of cardiac arrhythmias in these patients and also analyzed whether there are differences between the prevalence of types of arrhythmias in patients with heart disease and those with a structurally normal heart. The studied group comprises patients registered in the database of the Pediatric Cardiology Discipline, from January 1, 1996 to December 31, 2019. Their data were analyzed and subjected to appropriate statistical evaluation, considering a significance level of 5%. The variables analyzed were: Sex; Age; Type of Arrhythmia; Presence or not of Associated Heart Diseases. A total of 365 patients diagnosed with arrhythmia were evaluated, of which 15.9% had heart disease and 84.1% did not have heart disease. In patients with heart disease, there was no difference between the sexes, whereas in the group of patients without heart disease, there was a predominance of males. It was concluded that the most prevalent arrhythmias were atrial extrasystoles, ventricular extrasystoles and total atrioventricular block, considering both sexes. In females, the most prevalent were total atrioventricular block, atrial extrasystoles and ventricular extrasystoles. In males: ventricular extrasystoles, atrial extrasystoles and paroxysmal supraventricular tachycardia.